Ant manipulation in agro- and forest-ecosystems - Majer, Jonathan (1982)
Ants, because they are frequently ecologically dominant, tenders of Homoptera, avid predators, vectors of pathogens, cutters of leaves, or simply domestic nuisances, are often a central consideration in pest control schemes. As far back as the 12th century attempts were made to use the tree nesting ant, Oecophylla smaragdina, to limit citrus pests in southern China (Way, 1954). The potential use of ants in biological or integrated pest control schemes has been reviewed by Lestan (1973) and Room (1973) for the tropics and by Acllung (1966) for wood ants (Formica spp.) in temperate forests. For the record, these reviews have not included the more recent studies of Finnegan (1975 and earlier papers) on the role of Fortlica spp. in Canadian forests J Kim and Murakami (1980 and earlier papers) on Formica yesensis in Korean pine forests and of Laine and Niemela (1980) on Formica aquilonia in Finnish mountain birch woodland.